Adrenal Ganglioneuroblastoma in Adults: A Case Report and Review of the Literature - Stefano Benedini; Giorgia Grassi; Carmen Aresta; Antonietta Tufano; Luca Fabio Carmignani; Barbara Rubino; Livio Luzi; Sabrina Corbetta (Case Reports in Endocrinology)
Incidentally discovered adrenal masses are very common given the increased number of imaging studies performed in recent years. We here report a clinical case of a 20-year-old woman who presented with left flank pain. Ultrasound examination revealed a contralateral adrenal mass, which was confirmed at computed tomography (CT) scan. Hormonal hypersecretion was excluded. Given the size (11 × 10 × 7 cm) and the uncertain nature of the mass, it was surgically removed and sent for pathological analyses. Conclusive diagnosis was ganglioneuroblastoma. Ganglioneuroblastoma is an uncommon malignant tumor, extremely rare in adults, particularly in females. This neoplasm is frequently localized in adrenal gland.